The Existence of Kerapatan Adat Nagari (KAN) in Society Decision Making: Case Study in Durian Tinggi - Zainal Fadri; Mhd. Alfahjri Sukri; Rindi Ramadhani (Alfuad: Jurnal Sosial Keagamaan, 2024)
In general, the aim of this research is to map the existence of the Kerapatan Adat Nagari (KAN) in Nagari Durian Tinggi. The specific objectives are analyzing the structure and function of the KAN and analyzing the degree of power of KAN in government decision making in nagari. This research uses qualitative methods, with a field study approach to collect data. Data was collected through in-depth interviews and observations. The data that has been collected is classified and then made into a code that answers the research questions. The answer to a research question is the results obtained and then reported into a research discussion. The manuscript resulting from this research also wants to be further developed as a form of academic reaction to the condition of KAN in several nagari based on the latest regional regulations, such as the dilemma of positioning the role of KAN which is feared to overlap with the role of the nagari government and also for education for the community in increasing policy on the position of the elements contained in the nagari, both government and non-government or elements of society.